Contamination and Control of Mycotoxins in Grain and Oil Crops - Chenchen Zhang; Zheng Qu; Jie Hou; Yanpo Yao (Microorganisms, 2024)
Mycotoxins are carcinogenic, teratogenic and mutagenic toxic compounds produced by some filamentous fungi, which are extremely harmful to corn, rice, wheat, peanut, soybean, rapeseed and other grain and oil crops, and seriously threaten environmental safety, food safety and human health. With the rapid increase in the global population and the expansion of the main crop planting area, mycotoxin contamination has increased year by year in agricultural products. The current review aimed to summarize the contamination status and harmful effects of major mycotoxins of grain and oil crops and the environmental factors that impact mycotoxin contamination. Further, control measures of mycotoxin contamination, especially the biological control strategies, were discussed.